2009
DOI: 10.1083/jcb.200901021
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proteins follow multiple pathways to the basolateral cell surface in polarized epithelial cells

Abstract: Newly synthesized apical and basolateral membrane proteins are sorted from one another in polarized epithelial cells. The trans-Golgi network participates in this sorting process, but some basolateral proteins travel from the Golgi to recycling endosomes (REs) before their surface delivery. Using a novel system for pulse–chase microscopy, we have visualized the postsynthetic route pursued by a newly synthesized cohort of Na,K-ATPase. We find that the basolateral delivery of newly synthesized Na,K-ATPase occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 58 publications
3
83
0
Order By: Relevance
“…Consistent with this possibility, we have demonstrated that ␣ 2B -AR and ␤ 2 -AR use different routes to move from the ER to the Golgi (25). Furthermore, a recent study has demonstrated that vesicular stomatitis virus glycoprotein and Na ϩ -K ϩ -ATPase follow different pathways to the basolateral cell surface in polarized cells (37). It is also possible that post-Golgi transport of ␣ 2B -AR and ␤ 2 -AR may be mediated through different transport vesicles that are differentially modulated by Rab8 GTPase.…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with this possibility, we have demonstrated that ␣ 2B -AR and ␤ 2 -AR use different routes to move from the ER to the Golgi (25). Furthermore, a recent study has demonstrated that vesicular stomatitis virus glycoprotein and Na ϩ -K ϩ -ATPase follow different pathways to the basolateral cell surface in polarized cells (37). It is also possible that post-Golgi transport of ␣ 2B -AR and ␤ 2 -AR may be mediated through different transport vesicles that are differentially modulated by Rab8 GTPase.…”
Section: Discussionsupporting
confidence: 64%
“…The tag binds covalently to O 6 -benzylguanine (BG), resulting in the irreversible transfer of the substituted benzyl group to the reactive thiol within the SNAP tag. BG derivatives bearing fluorophores, biotin, or other groups can be used to label a SNAP-tagged protein (Farr et al, 2009;Maurel et al, 2010;Sun et al, 2011;Lukinavičius et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…On endocytosis from the oligodendroglial plasma membrane, PLP strictly enters the LE/Lys compartment and is never observed in RE (Winterstein et al, 2008). In epithelial cells, it has been demonstrated that a subset of cargos transit through RE intermediates on their biosynthetic route from the Golgi to the cell surface (Ang et al, 2004;Cresawn et al, 2007;Desclozeaux et al, 2008;Farr et al, 2009). Interestingly, the basolateral transport of those cargos traversing RE depends on VAMP3 (Fields et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account our in vitro data, we, however, assume that redundant transport pathways compensate lack of VAMP3 and VAMP7 function to achieve delivery of PLP. The establishment of multiple surface trafficking pathways involving endosomal compartments and redundancy among SNAREs is common to cells with sophisticated membrane compartment organization such as epithelial cells, adipocytes, and neurons (Borisovska et al, 2005;Farr et al, 2009;Zhao et al, 2009), allowing the cells to maintain their major functions within the organ despite the loss of individual components.…”
Section: Role Of Vamp3 and Vamp7 In Myelinationmentioning
confidence: 99%